Service quality and mediating role of perceived value and international tourist satisfaction on tourist loyalty in 4- and 5- star hotels in Kuala Lumpur, Malaysia - Keshavarz, Yousef (2016)
Loyalty has become the most important strategic aim in the hotel industry. However,most customers do not like to revisit the same hotel. The marketing literature has recognized that service quality affects perceived value and customer satisfaction and they had significant determinants of customer loyalty. In the literature, it was also recognized that the Expectancy Disconfirmation Theory (EDT), Theory of Reasoned Action (TRA), and Comparison-Level Theory (CLT) were the main theories relevant in analyzing tourist loyalty.Based on the literature, the purpose of this study is to obtain an empirical understanding of international tourist loyalty in four and five-star hotels in Kuala Lumpur. A multi-level model was used as a framework for the analysis. The dimensions of service quality including process quality and outcome quality as perceived by hotel customers were identified through a literature review. Hypotheses were formulated and tested to (i) examine the effects of process quality and the outcome quality on perceived value, tourist satisfaction, and tourist loyalty and (ii) to determine if the perceived value and tourist satisfaction have direct effects on tourist loyalty and play a mediating role between process quality and outcome quality with tourist loyalty.The results of this research were based on the analysis of a sample of 417 international tourists who had stayed at four and five-star hotels in Kuala Lumpur,Malaysia. Support was found for the use of a multi-level model and the primary dimensions: process quality and outcome quality. The six dimensions of process quality (tangible, reliability, responsiveness, assurance, empathy, and convenience) and three dimensions of outcome quality (valence, waiting time, and sociability) as perceived by international tourists in four and five-star hotel, were identified.The statistical findings supported the notion that process quality and outcome quality had a direct effect on perceived value and tourist satisfaction, and an indirect effect on tourist loyalty through perceived value and tourist satisfaction. The results also indicated that process quality and outcome quality did not have a direct effect on tourist loyalty. Perceived value and tourist satisfaction mediated the relationship between process quality and outcome quality with tourist loyalty.The results of this study contributed to the service marketing theory by providing an empirically based insight into the service quality, perceived value,tourist satisfaction and tourist loyalty constructs in the Malaysian hotel industry. This study suggested a significant contribution to the existing knowledge presenting the role of process quality and outcome quality in the area of tourist loyalty by mediating the role of perceived value and tourist satisfaction.This research will assist the hotel industry management to expand and perform a service strategy in order to create higher perceived customer value and upgrade the tourists' levels of satisfaction that can create favourable loyalty.